Empirical Analysis on Factors Impacting on Intention to Use M-learning in Basic Education in Egypt - Ali, Reham Adel; Arshad, Muhammad Rafie Mohd (Athabasca University Press, 2018)
It is apparent that m-learning will continuously have a massive role in terms of development in teaching and learning methods for education. Student's intention to use this technology is the main factor that eventually leads to a success in implementing m-learning. The objectives of this particular research are to come up with the development and examination towards a research model to uncover the factors that have important effects on the intention to use mobile learning for basic education in Egypt. A research model was developed through extending the unified theory of acceptance and use of technology (UTAUT) by incorporating two additional factors namely; learners' autonomy (LA) and content quality design (CQD). A quantitative approach based on cross-sectional survey was used to collect data from 386 respondents.. The methodology used in this study was a Partial Least Squares (PLS) that was expected to test the model empirically. The results showcased that learners' autonomy (LA), performance expectancy (PE), facilitating conditions (FC), and social influence (SI) are significant in relation to behavioural intention (BI) to use m-learning while effort expectancy (EE) did not show the impact on intention to use mobile learning. The research also found that content quality design (CQD) affects significantly on performance expectancy (PE) and effort expectancy (EE). The possible development in future research and the limitations of the findings are also discussed later in this paper.